Impact of Beamforming Algorithms on the Actual RF EMF Exposure From Massive MIMO Base Stations - Marcin Rybakowski; Kamil Bechta; Christophe Grangeat; Pawel Kabacik (IEEE Access, 2023)
Base stations equipped with large multi-antenna systems and associated beamforming schemes provide large capacity and coverage. Massive multiple-input-multiple-output (MIMO) with beamforming was introduced as one of the enablers of 5G system performance, and this technology is evolving with the introduction of more advanced algorithms for spatial multiplexing. One of the most relevant conditions to support deployment of 5G base stations with massive MIMO is to assess realistic RF electromagnetic field exposure compliance distances leveraging the actual maximum approach introduced in IEC 62232:2022. This evaluation method takes into account the variability of traffic load and beam patterns used by the beamforming algorithm. This work investigates the impact of various beamforming schemes, like grid-of-beams, eigen-beamforming and zero-forcing, as well as various array antenna configurations on the evaluation of the power reduction factor used when implementing the actual maximum approach for RF electromagnetic field compliance assessment of massive MIMO base stations. The modelling results show that lower power reduction factors can be considered for eigen-beamforming and zero-forcing beamforming algorithms compared to grid-of-beam. The power reduction factor drop can be up to −4 dB when 8 user equipment’s are connected simultaneously.